Low-temperature magnetic and thermal properties of CePdSb - Trovarelli, O.; Sereni, J.G.; Schmerber, G.; Kappler, J.P.; Sereni, Julián (American Physical Society, 1994)
Fil: Trovarelli, O. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina